(untitled) (Revista Argentina de Musicología, 2023)
In Denis Diderot numerous and often contradictory writings on aesthetics and music we find continuous references to a conception of the figure of genius in which some of the features that would be consolidated during Romanticism are already outlined.. We start by studying the powerful aesthetical changes that happen during the last third part of the eighteen century. Consequently in order to examine Diderot’s conception of genius we have to deal with: the impossible attempt to rationally explain the human existence —despite the empirical evidence—, how the apparition of the genius is affected by external factors like education, the indispensable correlation between to be a genius and possess an eccentric personality or not to be a person ruled by the aesthetics conventions. Considering these statements we will tackle the position of women in society given by Diderot; as well as the conceptual category of genius is expressed in women’s personality.